2017
DOI: 10.5606/tgkdc.dergisi.2017.12775
|View full text |Cite
|
Sign up to set email alerts
|

The role of current surgical therapy for pediatric/adolescent and adult patients with bronchiectasis

Abstract: ÖZAmaç: Bu çalışmada, bronşektazili çocuk ve erişkin hastalarda klinik bulgular, cerrahi endikasyonlar, cerrahi işlemler, ameliyat sonrası komplikasyonlar ve cerrahi tedavi sonuçları karşılaştırıldı.Ça lış ma pla nı: Ocak 2000 -Aralık 2013 tarihleri arasında bronşektazi nedeni ile Göğüs Cerrahisi bölümünde ameliyat edilen toplam 99 hasta (40 erkek, 59 kadın; ort. yaş 33.3 yıl; dağılım 10-67 yıl) geriye dönük olarak incelendi. Grup 1 (n=28) çocuk hastalardan (≤18 yıl) ve grup 2 (n=71) erişkin hastalardan (>18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(85 reference statements)
1
0
0
Order By: Relevance
“…In previous studies, complete recovery rates of symptoms after surgical treatment of bronchiectasis were reported as 82.1% in children and 88.7% in adults. [9] In this study, the rate of disappearance of symptoms, suggestive of complete recovery, was found to be 72.2%, consistent with the literature. The most important factor affecting the complete disappearance of symptoms after surgical treatment is that whether the resection is anatomic or not.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, complete recovery rates of symptoms after surgical treatment of bronchiectasis were reported as 82.1% in children and 88.7% in adults. [9] In this study, the rate of disappearance of symptoms, suggestive of complete recovery, was found to be 72.2%, consistent with the literature. The most important factor affecting the complete disappearance of symptoms after surgical treatment is that whether the resection is anatomic or not.…”
Section: Discussionsupporting
confidence: 91%